Genotype and Sex Effect on Gastrointestinal Nutrient Content, Microflora and Carcass Traits in Nigerian Native Chickens - Peters, Sunday O.; Idowu, Olusegun M.O.; Agaviezor, Brilliant O.; Egbede, Raphael O.; Fafiolu, Adeboye O. (International Journal of Poultry Science, 2010)
The nutrient concentration of crop and gizzard contents of three genotypes of indigenous scavenging chickens under rural conditions were investigated along-side with the micro-flora community of the Gastrointestinal Tract (GIT), body dimensions and carcass traits. Genotype significantly (p<0.01) affected the Crude Protein (CP) and Dry Matter (DM) values while Ether Extract (EE) value was significantly (p<0.05) influenced by sex of bird. The interaction between genotype and sex significantly (p<0.01) affected only CP and EE values while Crude Fibre (CF), ash and Gross Energy (GE) values were statistically similar across both genotype and sex of the bird. The genotype significantly (p<0.01) affected Live Weight (LWT), Bled Weight (BDWT), Plucked Weight (PLWT), Dressed Weight (DRWT), Breast Girth (BRG), liver weight, lung weight, heart weight, GIT weight and GIT length. The sex of bird also significantly (p<0.01) influenced Body Length (BLT), LWT, BDWT, PLWT, BRG, shank length, keel length, heart weight, gizzard weight, lung weight and GIT length while the interaction between genotype and sex significantly (p<0.05) affected LWT, BDWT, PLWT, DRWT, BRG, heart weight, gizzard weight and lung weight. Both genotype and sex significantly (p<0.01) influenced bacteria population of the chickens caeca. Salmonella sp., Escherichia coli and Staphylococcus aureus were prevalent in the caeca of all the scavenging birds. It was concluded that there are genotype and sex effects on crop and gizzard content, linear body measurements and presence or absence of bacteria in the caeca of the Nigerian native chickens raised under rural extensive system This findings further corroborates the abundance of genetic variation that can be exploited in developing any stock improvement programme for growth, carcass or disease resistance traits involving the Nigerian local chickens.